Micromanufacturing of Metallic Materials - Zhao, Jingwei; Jiang, Zhengyi; Dobrzański, Leszek Adam; Lee, Chong Soo; Yu, Fuxiao (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Product miniaturization is a trend for facilitating product usage, enabling product functions to be implemented in microscale geometries, and aimed at reducing product weight, volume, cost and pollution. Driven by ongoing miniaturization in diverse areas, including medical devices, precision equipment, communication devices, micro-electromechanical systems and microsystems technology, the demands for micro metallic products have been tremendously increased. Such a trend requires the development of advanced technology for the micromanufacturing of metallic materials, with regard to producing high-quality micro metallic products that possess excellent dimensional tolerances, the required mechanical properties and improved surface quality. Micromanufacturing differs from conventional manufacturing technology in terms of materials, processes, tools, and machines and equipment, due to the miniaturization nature of the whole micromanufacturing system, which challenges the rapid development of micromanufacturing technology. Such a background has prompted and encouraged us to publish a scholarly book on the topic of the micromanufacturing of metallic materials, with the purpose of providing readers with a valuable document that can be used in the research and development of micromanufacturing technology. This book will be useful for both theoretical and applied research aimed at micromanufacturing technology, and will serve as an important research tool, providing knowledge to be returned to the community not only as valuable scientific literature, but also as technology, processes and productivities.